DISTRIBUTION MODELING OF RATTAN RAW MATERIALS WITH DYNAMICS SYSTEM APPROACH - Kumala Dewi - NIM : 34212302, Nurlaela
Scarcity of raw rattan has occurred since the Decree of Minister of Trade No. 35 / M-Dag / Per / 11/2011 issued. The decree prohibited export of raw rattan since 20th of December 2011. The reason behind the ban on rattan exports for the Minister of Trade is to empower the domestic industry. After the Decree is valid, there is expectation that the rattan raw materials will be easy to obtain or the occurrence of Over Supply (Because the production of rattan is 300 to 400 thousand tons per year, while the domestic industry needs only 15-30 thousand tons). But in reality, the rattan industry has trouble getting raw materials. Currently, supply policy involves all sections, ranging from farmers' locations, collectors, traders, and wholesalers have a very imporant role in the supply of rattan raw materials for the rattan furniture industry. The difficulty in obtaining rattan raw materials in rattan-producing areas has caused the rattan industry to fall by 30% of the total national rattan industry in Indonesia. From several previous studies, the study of transportation paths that developed so far is more about the distance traveled, routes, transport capacity, delivery time and costs incurred. Regarding the behavior and causal relationships between variables that form the distribution system, no one has examined until now. The distribution channel model of supply of raw materials of rattan has the purpose to distribute rattan raw materials from upstream to downstream. This research focuses more on the policy on raw material price of raw rattan, dry raw material selling price and distribution activities which are expected to lead to efficient transportation costs, good supply service performance and in accordance with policies related to rattan trading and components of distribution cost inflicted. Methodology of this research was using dynamics system with simulation. The results obtained from model validation of rattarn raw material data variable of Katingan Tengah district showed that the closeness of simulation results with historical data has been close enough and R2 obtained is equal to 0.969. The proposed scenarios are: the growth pattern is maintained as before, raises the income level of farmers, collectors and rattan traders in Katingan Regency, policy of fuel oil (BBM) 1 (one) price from upstream to downstream of rattan transport transportation and subsidizes the distribution costs for the transportation of forest products, especially rattan in Katingan Regency. The result of the research for scenario that the growth pattern is maintained as before will make the rattan raw material in rattan market disappear, with the policy of Katingan Regency Government give subsidy for transportation cost from upstream (forest) to collecting place in village will impact to the increase of income of farmers, collector, PT. KJM, Large Traders Katingan and also will increase the demand for rattan raw materials because the selling price of rattan raw materials is still affordable by downstream rattan industry. A revolutionary policy on the price of fuel (BBM) of 1 (one) price for rattan transport turned out to have a pretty good impact on the increase in movement throughout the distribution of raw materials because transportation costs became cheap. The process of planning the distribution channels has never considered the causal relationships that occur between the players who are in distribution channels so that the impact on the tranporation system is not efficient. The distribution line model recommended through this research is able to accommodate policies and can be simulated so that it can predict its impact or results in the long term or short term.